Informatics and Computerized Tomography Aiding Detection and Diagnosis of Solitary Lung Cancer - Silva, Aristófanes Corrêa; Paiva, Anselmo Cardoso; Nunes, Rodolfo Acatauassu; Gattass, Marcelo (IntechOpen, 2011)
None